Collaborative Learning Platforms for Promoting Edupreneurship in Underprivileged Regions - Basri, Hasan; Evadianti, Yuli; Seftiani, Rafika; Zakaria, Noor Azura; Jacqueline, Greisy (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study examines the potential of collaborative learning platforms to promote edupreneurship in underprivileged regions, with a specific focus on the role of persuasive communication by volunteers at Gubuk Literasi. During the COVID-19 pandemic, increased smartphone usage led to a notable decline in children reading interest, particularly in rural areas. Gubuk Literasi addresses this issue by fostering a reading culture through innovative volunteer-driven approaches that emphasize personalized communication, engaging language, and effective time management. This research employs a qualitative methodology, collecting both primary and secondary data through observation, interviews, and documentation. The findings reveal that persuasive communication significantly influences children willingness to read, with strategies such as active listening, collaborative discussions, and reward systems proving particularly effective. This study underscores the importance of volunteer efforts in creating an inclusive and sustainable learning ecosystem. By leveraging collaborative platforms, initiatives like Gubuk Literasi not only enhance literacy but also serve as a model for edupreneurship, empowering communities to address educational disparities and drive socio-economic growth in underprivileged regions. These insights contribute to a broader understanding of how localized educational innovations can align with global development goals, providing actionable strategies for expanding access to quality education.